Regarding the Establishment, Needs and Possibilities for Further Development of the Criminal Legal Protection of the Environment - Joldžić, Vladan; Stanković, Vera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
As a complex area, environmental law requires a responsible and long-term, comprehensive approach and cooperation, especially in relation to criminal law and problems in criminal legal reactions to those activities that are contrary to the prescribed obligations relevant to the protection of the environment, which are the subject of this paper. The elements of the base and the development of the criminal-legal reaction to undesirable and illegal threats and violations of real ecological crimes are analysed, which, in the end, affect the human right to a healthy life. The aim of the article is centred on understanding the pathways of formation and further development of the criminal legal reaction against threats and violations of environmental rights, obligations and responsibilities, particularly in the field of the Republic of Serbia. Also proposed are possible ways for further development of the Criminal Code of the Republic of Serbia.